2018
DOI: 10.1093/jxb/ery302
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis UMAMIT24 and 25 are amino acid exporters involved in seed loading

Abstract: UMAMIT24 and UMAMIT25 are expressed in distinct seed tissue during Arabidopsis embryogenesis, and are both involved in amino acid transfer to the seed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 66 publications
(94 reference statements)
2
42
0
1
Order By: Relevance
“…Amino acids import into and export out of the vacuole requires the activity of transporters. Several amino acid transporters belonging to different families have been found to be localized on the tonoplast [56,73,76]. AtAVT3 family members are homologs of AtANT1 but localized to the vacuolar membrane in Arabidopsis [76].…”
Section: Intracellular Translocation Of Amino Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acids import into and export out of the vacuole requires the activity of transporters. Several amino acid transporters belonging to different families have been found to be localized on the tonoplast [56,73,76]. AtAVT3 family members are homologs of AtANT1 but localized to the vacuolar membrane in Arabidopsis [76].…”
Section: Intracellular Translocation Of Amino Acidsmentioning
confidence: 99%
“…Repression of its expression has no impact on seed set, but seed volume is significantly decreased [ 14 ]. The tonoplast-localized AtUMAMIT24 was found mainly in the chalazal seed coat and may be involved in temporary storage of amino acids in chalaza [ 73 ]. AtUMAMIT25 is targeted to endosperm cells, indicating its role in amino acid export from the endosperm [ 73 ].…”
Section: Amino Acid Transport Processes Mediated By Amino Acid Tramentioning
confidence: 99%
“…Though the vascular trace of the funiculus terminates at the funiculus‐CZSC interface in Arabidopsis , the vascular system penetrates the CZSC in B. napus (Millar et al ). Furthermore, transport linking the maternal and filial regions have also been reported in Arabidopsis and genes associated with the transport of amino acids (Besnard et al ) and phosphates (Vogiatzaki et al ) have been shown to preferentially accumulate in the chalazal end of the seed. Thus, the chalazal pole of B. napus may function as a gateway for nutrient unloading and seed filling thereby guiding developmental processes.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that the AAP family members play critical roles in plant growth, organ development, and abiotic and biotic stress responses [4][5][6][7]. However, there have been few systematic studies on AAPs in B. napus so far.…”
Section: Discussionmentioning
confidence: 99%
“…AAs derived from senescent leaves are the major N forms for seed N nutrients [3]. Therefore, efficient uptake and translocation of AAs are favorable for yield production, and also favorable for plant resistance against various stresses [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%